Total sanitation : a community stake - Mohiuddin, Helal; Ayub Ali, Md.; Halder, Joseph; Community-led Total Sanitation (Programme); NGO Forum for Drinking Water Supply and Sanitation (Bangladesh) (Dhaka : NGO Forum for Drinking Water Supply & Sanitation, 2005)
Study and survey of Community-led Total Sanitation (Programme) (CLTS) with reference to Bangladesh.
Includes bibliographical references (p.115-116).
Keywords: Community-led Total Sanitation (Programme); Sanitation -- Bangladesh; Water-supply -- Bangladesh; Public health -- Bangladesh